A benign approach for novel synthesis of Eu3+ doped MgNb2O6: Its photoluminescence and photocatalytic studies. Issue 10 (15th May 2021) - Basavaraju, N.; Prashantha, S.C.; Nagabhushana, H.; Chandrasekhar, M.; Kumar, A. Naveen; Shekhar, T.R. Shashi; Ashwini, S.; Anantharaju, K.S.
Abstract: The Present work involves the production of Eu 3+ (1–11 mol %) doped MgNb2 O6 nanophosphors (NPs) by combustion technique using ODH as a fuel for the first time and well characterized. The average crystallite and the energy gap of the samples were found to be in the range of 20–45 nm and 4.65–5.66 eV respectively, TEM results reflects the same crystallite size values. The effect of doping was confirmed by the characteristic emission peaks recorded at 535, 590, 614, 642 and 698 nm may be attributed to the 4f–4f intra shell transitions ( 5 D0 → 7 Fj=0, 1, 2, 3, 4 ) of Eu 3+ cations when bombarded at 395 nm energy. Judd–Ofelt parameters (Ω2, Ω4 ), transition probabilities (AT ), quantum efficiency (η), luminescence lifetime (τrad ) are discussed in detail. From the emission spectra, CIE (Commission International de I' Eclairage) chromaticity co-ordinates and Correlated color temperature (CCT) were estimated. Langmuir-Hinshelwood model was used to study the photocatalytic degradation of AR-88 dye. The above results confirmed that the present phosphor can be potentially used for display and photocatalytic applications.